A CAD/CAM Zirconium Bar as a Bonded Mandibular Fixed Retainer: A Novel Approach with Two-Year Follow-Up. (27th July 2017) - Zreaqat, Maen; Hassan, Rozita; Hanoun, Abdul Fatah
Abstract : Stainless steel alloys containing 8% to 12% nickel and 17% to 22% chromium are generally used in orthodontic appliances. A major concern has been the performance of alloys in the environment in which they are intended to function in the oral cavity. Biodegradation and metal release increase the risk of hypersensitivity and cytotoxicity. This case report describes for the first time a CAD/CAM zirconium bar as a bonded mandibular fixed retainer with 2-year follow-up in a patient who is subjected to long-term treatment with fixed orthodontic appliance and suspected to have metal hypersensitivity as shown by the considerable increase of nickel and chromium concentrations in a sample of patient's unstimulated saliva. The CAD/CAM design included a 1.8 mm thickness bar on the lingual surface of lower teeth from canine to canine with occlusal rests on mesial side of first premolars. For better retention, a thin layer of feldspathic ceramic was added to the inner surface of the bar and cemented with two dual-cured cement types. The patient's complaint subsided 6 weeks after cementation. Clinical evaluation appeared to give good functional value where the marginal fit of digitized CAD/CAM design and glazed surface offered an enhanced approach of fixed retention.